Utilizing Canva in Developing Creative Teaching Materials to Enhance the Professionalism of Elementary School Teacher Education Students - Airinita Airinita; Kasih Ulia Safitri; Indah Permata Sari (Institution of Scientific Publishing and Publication of the Yayasan Dzaky Elmumtaz Qurani, 2026)
This study aims to analyze the utilization of the Canva application in developing creative teaching materials and its impact on the professionalism of Elementary School Teacher Education (PGSD) students at Nahdlatul Ulama University, West Sumatra. Originality: Unlike previous studies that focused solely on media effectiveness, the novelty of this research lies in the integration of the Canva platform as an instrument to strengthen four indicators of pre-service teacher professionalism: pedagogical, personal, social, and professional competencies within a single media development workflow. Methodology: A descriptive qualitative method was employed involving 30 sixth-semester students selected through a purposive sampling technique based on basic digital literacy criteria. Data were collected through participatory observation, in-depth interviews, and digital portfolio documentation. Systematic data analysis was conducted using the Miles and Huberman model, encompassing data reduction, data display (coding and categorization), and conclusion drawing. To ensure data validity and minimize subjectivity bias, this study applied technical triangulation and member checks. Findings: The results indicate that the utilization of Canva significantly enhances student professionalism through: (1) improved pedagogical ability in designing content based on elementary students' characteristics; (2) mastery of adaptive instructional technology; and (3) creativity in producing communicative and contextual teaching materials. These findings confirm that mastery of digital design is not merely an additional skill but an integral element in forming the professional identity of pre-service teachers in the digital age.